Remote Digital Solutions for Organization of Treatment and Monitoring of Patients with Heart Failure Abroad - N. N. Kamynina; D. A. Andreev (Здоровье мегаполиса)
Introduction. Cardiovascular pathology is one of the leading causes of global mortality burden, being responsible for more than 30% of all deaths. Continuous monitoring of patients with heart failure is crucial in developing measures aimed at reducing cardiovascular mortality. The advancement of digital technologies in this field will improve the quality of monitoring and treatment of patients with heart failure.Objective. The goal of the study was to summarize the results of implementation of some well-known approaches to digital healthcare for patients with heart failure.Materials and methods. The data is obtained from PubMed databases and Google search results. Scientific articles in English were selected by the following keywords: “heart failure”, “information technologies”, “remote monitoring”, “digital technologies”, etc. In some cases, the search was also conducted in еру Russian Internet segment using such keywords as “сердечная недостаточность [heart failure]”, “распространенность [prevalence]”, etc.Results. The use of digital technologies for recording health indicators in people with heart failure has been examined. The aspects of self-monitoring of health indicators are considered, examples of sensor and artificial intelligence technologies for continuous remote monitoring of patients are given, the principles of digital patient management for achieving adherence to treatment are presented, aspects of remote rehabilitation using telehealth technologies are discussed. Discussion. New elements of digital health provide a wide range of opportunities. Although the approaches listed in this paper are promising, further study of their effectiveness in controlled trials and in real practice is needed. It is necessary to continue developing the concept of continuous monitoring of patients with heart failure. Research programs should take into account all the possibilities of modern technologies in order to find and standardize the best approaches.